Timestamp-Based Secure Shield Architecture for Detecting Invasive Attacks - Bae, Junyeong; Oh, Junseok; Lee, Myoung Jin; Lee, Young-woo (IEEE transactions on very large scale integration (VLSI) systems, 2023)
The design-for-security (DFS) methodology protects hardware and systems from physical attacks on chips while incorporating additional circuits to detect potential security risks. Microprobing and focused-ion-beam (FIB) circuit editing, which are known for their significant invasiveness among physical attacks, are regarded as highly powerful methods to access security-related information directly. The DFS methodology involves continually developing various techniques to defend chips against such attacks. Generally, previous studies compare the arrival times of two signals to detect microprobing and compare the encrypted input-output data to detect circuit editing. In this study, we propose an innovative DFS methodology that records the timings of round-trip signals, which may arrive early or late due to microprobing or FIB circuit editing. This technique can help detect both types of attacks within a single clock cycle while maintaining minimal hardware overhead, even with an increase in the protected area. The proposed methodology considers both miniaturization and security, and it is expected to contribute to the advancement of security-related technologies and strategies.